Sources Of Administrative Leadership Strength And Its Relationship With Training Of Human Resources - Nasser Habtoor; Ali Ramadan Musbah; Marai A. D. Abdalla (Leena and Luna International (Pvt) Limited, 2024)
Asian Journal of Management Sciences & Education Vol. 4(1) January 2015